Effectiveness of the Strategies Implemented in Sri Lanka for Controlling the COVID-19 Outbreak - K. K. W. H. Erandi; A. C. Mahasinghe; S. S. N. Perera; S. Jayasinghe (Journal of Applied Mathematics)
In order to bring the new coronavirus pandemic in the country under control, the government of Sri Lanka implemented a set of control strategies including social distancing, quarantine, lockdowns, travel restrictions, and isolation of villages. The aim of this study is to investigate the effectiveness of the overall control process with the aid of classical compartment models and network models. Our results indicate that the prevailing control strategies are effective with at least 50% contact rate reduction or with at least 40% isolation of the contact history of infected population.